Evaluation of pre-emergent herbicides for weed control in cotton (Gossypium hirsutum L.) (Agro Productividad, 2025)
Objective: To assess the efficacy of various pre-emergence herbicides for weed control in conventional cotton crops under the environmental and agronomic conditions of Chihuahua State, Mexico, aiming to identify alternatives that minimize dependence on repeated applications and extend the duration of control.Design/Methodology/Approach: The trial was conducted at the Delicias Experimental Station (INIFAP) using a randomized complete block design with four replications. Four pre-emergence herbicides Fomesafen, Trifluralin, S-Metolachlor, and Pendimethalin alongside three controls (glyphosate [regional standard], cultural control, and an untreated weedy check) were evaluated across seven conventional cotton varieties. Weed control was measured at 15, 21, 30, 40, and 50 days after application (DAA), employing the European Weed Research Society (EWRS) rating scale.Results: Fomesafen, Trifluralin, and S-Metolachlor achieved over 96.5% control within the first 30 days, categorized as "very good control." Although efficacy declined by 50 DAA, it remained above 85%. Pendimethalin exhibited strong initial control but its effectiveness diminished more rapidly. Glyphosate demonstrated moderate control, which significantly declined by 30 DAA. The untreated checks showed poor to negligible weed suppression.Limitations/Implications: The study evaluated only a single herbicide application per cropping cycle, without incorporating post-emergence or sequential pre-emergence treatments, thereby limiting the scope for evaluating long-term integrated weed management strategies.Findings/Conclusions: The tested pre-emergence herbicides provided effective weed control during cotton’s critical competition period. Their integration into broader weed management programs is recommended to delay the onset of herbicide resistance and enhance overall control efficacy.